Remarks at the International Corruption Hunters Alliance Meeting, Washington, D.C., December 8, 2014 - Kim, Jim Yong (2016)
Jim Yong Kim, President of the World Bank Group, discusses two goals: to end extreme poverty by 2030 and to boost shared prosperity for the bottom 40 percent of the Population. These efforts require us fight against corruption in its many forms. He talks about the need to be alert, respond immediately when things go wrong, learn from the experience, and assure it doesn’t happen again. He cautions about the lack of governance, which is a necessary condition for corruption to thrive. The challenge is to get the knowledge and tools to the right people at the right time, and to fully leverage opportunities for reform. World Bank, with support from Australia, Denmark and Norway, created the International Corruption Hunters Alliance to engage in what is happening at a multilateral level, to provide access to the latest anti-corruption tools and information, and to create the dialogue that drives our collective effort to beat corruption. He concludes by saying that the intersection with corruption and dirty money are undeniable, and the implications for sustainable, inclusive development are clear.